Informatics in Schools. Beyond Bits and Bytes: Nurturing Informatics Intelligence in Education - Jean-Philippe Pellet; Gabriel Parriaux (Springer Nature Switzerland, 2023)
This book constitutes the proceedings of the 16th International Conference on Informatics in Schools: Situation, Evolution and Perspectives, ISSEP 2023, held in Lausanne, Switzerland, during October 23–25, 2023. The 14 full papers presented in this book were carefully reviewed and selected from 47 submissions. They are organized in four topical sections named: artificial intelligence and its applications; competitions, problem solving, and computational; robotics and unplugged modalities; and curricula and computer science concepts. This is an open access book.